Impacts of different types of straw returning on soil physicochemical properties, microbial community structure, and pepper quality - Xiapu Gai; Biao Chen; Shijuan Xiong; Qingqing Zhou; Yuan Yuan; Yumei Mou (Frontiers in Plant Science)
IntroductionStraw returning serves as a critical agronomic practice for soil quality improvement and sustainable agricultural development. However, the differential regulatory mechanisms of cellulose-rich (e.g., pepper straw) versus lignin-rich (e.g., mulberry stem) straw types on soil physicochemical properties, microbial community structure, and crop nutritional quality remain poorly understood, particularly in pepper cultivation regions of Karst mountainous.MethodsIn this study, taken the pepper planting soil as research object, the treatments of cellulose pepper straw (CS), lignin mulberry stem (MS) and control (CK) were set up. By measuring soil nutrients, microbial community diversity and pepper nutritional quality indicators, combined with high-throughput sequencing technology, the ecological effects of different types of straw returning were systematically analyzed.Results and discussionThe results showed that CS treatment significantly increased nitrate nitrogen content and available potassium, but decreased organic matter content by 8% and microbial biomass nitrogen by 65.5%. MS treatment significantly increased soil organic matter and microbial biomass carbon, and promoted the increase of amino acid content by 59.6%. Microbial community analysis showed that Pseudomonas had the highest values in all three treatments, CS treatment enriched Actinomycetota, while MS treatment inhibited Acidobacteriota. Correlation analysis revealed that the functions of bacteria and fungi were positively correlated with SOC, NO3–N, AP, TK, MBN, and EC, reaching a significant level with MBN (P<0.05). However, they showed negative correlation with NH4+-N. It indicated that straw types drive microbial functional differentiation by regulating nutrient availability. The results of chili quality showed that CS treatment significantly increased capsaicin (16.5%) and crude fiber (21.4%), but reduced reducing sugar (13.3%). MS treatment increased amino acids (59.6%) and crude fat (6.3%), which was related to the different metabolic pathways caused by the difference in carbon-nitrogen ratio. In summary, cellulose-based straw enhances nutrient availability through short-term mineralization, indicating that carbon pool loss and nitrogen imbalance risks might limit long-term soil health. However, lignin-based straw maintains long-term soil health through carbon sequestration and microbial homeostasis, which provides a theoretical basis for the utilization of straw resources in karst areas and the improvement of quality and efficiency of pepper industry.